Large-diameter trees, snags, and deadwood in southern Utah, USA - Lutz, James A.; Struckman, Soren; Furniss, Tucker J.; Birch, Joseph D.; Yocom, Larissa L.; McAvoy, Darren J. (Ecological processes, 2021)
Background The epidemic Dendroctonus rufipennis (spruce beetle) outbreak in the subalpine forests of the Colorado Plateau in the 1990s killed most larger Picea engelmannii (Engelmann spruce) trees. One quarter century later, the larger snags are beginning to fall, transitioning to deadwood (down woody debris) where they may influence fire behavior, regeneration, and habitat structure. Methods We tracked all fallen trees ≥ 1 cm in diameter at breast height (1.37-m high) and mapped all pieces of deadwood ≥ 10-cm diameter and ≥ 1 m in length within 13.64 ha of a high-elevation mixed-species forest in the Picea–Abies zone annually for 5 years from 2015 through 2019. We examined the relative contribution of Picea engelmannii to snag and deadwood pools relative to other species and the relative contributions of large-diameter trees (≥ 33.2 cm at this subalpine site). We compared spatially explicit mapping of deadwood to traditional measures of surface fuels and introduce a new method for approximating vertical distribution of deadwood. Results In this mixed-species forest, there was relatively high density and basal area of live Picea engelmannii 20 years after the beetle outbreak (36 trees ha −1 and 1.94 m 2 ha −1 ≥ 10-cm diameter) contrasting with the near total mortality of mature Picea in forests nearby. Wood from tree boles ≥ 10-cm diameter on the ground had biomass of 42 Mg ha −1 , 7 Mg ha −1 of Picea engelmannii , and 35 Mg ha −1 of other species. Total live aboveground biomass was 119 Mg ha −1 , while snag biomass was 36 Mg ha −1 . Mean total fuel loading measured with planar transects was 63 Mg ha −1 but varied more than three orders of magnitude (0.1 to 257 Mg ha −1 ). Planar transects recorded 32 Mg ha −1 of wood ≥ 7.62-cm diameter compared to the 42 Mg ha −1 of wood ≥ 10-cm diameter recorded by explicit mapping. Multiple pieces of deadwood were often stacked, forming a vertical structure likely to contribute to active fire behavior. Conclusion Bark beetle mortality in the 1990s has made Picea an important local constituent of deadwood at 20-m scales, but other species dominate total deadwood due to slow decomposition rates and the multi-centennial intervals between fires. Explicit measurements of deadwood and surface fuels improve ecological insights into biomass heterogeneity and potential fire behavior.